Effects of Pilates method on abdominal diastasis after pregnancy (Research, Society and Development, 2021)
Physiological abdominal diastasis affects most women during the gestational period due to the increased circumference of the abdomen, necessary for the development of the fetus to occur, however, if the separation of the rectus abdominis becomes exacerbated, abdominal diastasis begins to classify if pathological and may result in damage to women's health and self-esteem. Therefore, the aim of this article is to present the Pilates method as a treatment for abdominal diastasis after pregnancy, through research carried out on the Academic Google, PubMed and Scientific Electronic Library Online (Scielo) platforms, in search of scientific articles published between the years of 2015 and 2021. Through the research carried out, it is possible to obtain that the Pilates method through its principles and techniques, with emphasis on contraction of muscles named power house, it's able to reduce the distance between rectus abdominis muscles bundles muscles', which may thus, be an important resource in the treatment of abdominal diastasis after the gestational period.